Assuring Quality Teacher Education: Preparing Science Teachers for Blended Classrooms - Kalu-Uche, Nnennaya; Adolphus, Telima (West African Journal of Open and Flexible Learning, 2023)
The advent of Information and Communication Technology and the continued acceptance and advancement of online learning following the COVID-19 pandemic has placed demands for unique competencies and skills on teachers if they are to succeed in their career. This study investigated the extent to which science teacher preparation programmes in South-East Nigeria incorporate Blended Learning. Two hundred and ten (210) pre-service science teachers and Thirty-two (32) science teacher educators in three federal government-owned universities in South-East Nigeria made up the sample for the study. The instrument for data collection, which had different versions for teacher educators and pre-service science teachers, and Cronbach Alpha reliability coefficient of 0.86 and 0.81 respectively, was a 21-item researcher-developed instrument titled Blended Learning in Science Teacher Preparation Questionnaire (BLiSTPQ). Three research questions and two hypotheses guided the study. Results indicated that blended learning is not generally adopted in pre-service science teacher preparation in Federal Government-owned universities in South-East Nigeria. Based on the findings of the study, it was recommended, among others, that teacher education programmes should adopt learning management systems to provide hands-on learning and training opportunities on the use of blended learning to pre-service science teachers. Résumé L’avènement des technologies de l’information et de la communication ainsi que l’acceptation et le progrès continus de l’apprentissage en ligne après la pandémie de COVID-19 ont imposé aux enseignants des exigences de compétences et d’aptitudes uniques s’ils veulent réussir dans leur carrière. Cette étude a examiné dans quelle mesure les programmes de préparation des enseignants de sciences au sud-est du Nigeria intègrent l’apprentissage hybride. Deux cent dix (210) enseignants de sciences en formation et trente-deux (32) formateurs d’enseignants de sciences dans trois universités publiques fédérales de la region du sud-est du Nigéria constituaient l’échantillon de l’étude. L’instrument de collecte des données, dont les versions étaient différentes pour les formateurs d’enseignants et les enseignants de sciences en formation initiale, et dont le coefficient de fiabilité Cronbach Alpha était respectivement de 0,86 et 0,81, était un instrument de 21 questions élaboré par le chercheur et intitulé Blended Learning in Science Teacher Preparation Questionnaire (BLiSTPQ) (Questionnaire sur l’apprentissage mixte dans la préparation des enseignants de sciences). Trois questions de recherche et deux hypothèses ont guidé l’étude. Les résultats ont indiqué que l’apprentissage hybride n’est généralement pas adopté dans la formation initiale des enseignants de sciences dans les universités fédérales du sud-est du Nigeria. Sur la base des résultats de l’étude, il a été recommandé, entre autres, que les programmes de formation des enseignants adoptent des systèmes de gestion de l’apprentissage pour offrir aux enseignants de sciences en formation des opportunités d’apprentissage et de formation pratiques sur l’utilisation de l’apprentissage hybride. Mots-clés : Assurance Qualité, Apprentissage Hybride, Enseignement Scientifique, Formation des Enseignants